RELEVANSI MAKNA JIHAD TERHADAP PANDEMI COVID-19: ANALISIS MA’NA CUM MAGZHA Q.S. AL-‘ANKABUT (29): 6 - Sholihah, Amilatu (Academic Journal of Islamic Principles and Philosophy, 2021)
This article discusses the meaning of jihad in QS. Al-'Ankabut: 6-7 and its relevance in preventing the covid-19 virus. This type of research is literature, using qualitative descriptive-analytical methods with the Ma'nÄ Cum MagzhÄ approach, namely by describing the meaning of jihad in the 7th century (linguistic analysis), looking at asbabun nuzul (historical analysis), the relationship of verses with other verses/munasabah verse (intratextual analysis), the relationship of the verse with the text outside the Qur'an (intertextual analysis), the meaning of the verse (maghza dates), and contextualization of the verse with the present era (maghza al-mutkharik al-mu'ashir). This study will focus on three aspects of the discussion, firstly related to the original meaning of jihad which was seen in the 7th century, namely when the Qur'an was revealed, Second, discussing the original meaning of jihad contained in QS. Al-'Ankabut: 6-7. The third explains the relevance of the meaning of jihad to current contemporary issues, namely COVID-19. The results of this study indicate that the first jihad is the ability to be serious in the face of difficulties or trials in fighting enemies, demons, and against oneself, namely fighting lust with the sole purpose of seeking the pleasure of Allah SWT. The second jihad in QS. Al-'Ankabut verses 6-7 are jihad to do good, do good deeds, and preach to invite mankind to convert to Islam, and be patient in facing trials. The third relevance of the meaning of jihad to the current contemporary issue, namely covid-19, can be seen when someone tries to fight jihad against COVID-19, namely by complying with government regulations such as self-isolation, PSBB, physical distancing, and implementing a healthy lifestyle. In addition, it also strives in terms of spirituality by doing good deeds such as practicing special prayers to avoid the plague and getting closer to Allah SWT.